2016
DOI: 10.1038/srep29506
|View full text |Cite
|
Sign up to set email alerts
|

Implementing rapid, robust, cost-effective, patient-centred, routine genetic testing in ovarian cancer patients

Abstract: Advances in DNA sequencing have made genetic testing fast and affordable, but limitations of testing processes are impeding realisation of patient benefits. Ovarian cancer exemplifies the potential value of genetic testing and the shortcomings of current pathways to access testing. Approximately 15% of ovarian cancer patients have a germline BRCA1 or BRCA2 mutation which has substantial implications for their personal management and that of their relatives. Unfortunately, in most countries, routine implementat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
284
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 184 publications
(303 citation statements)
references
References 36 publications
14
284
2
3
Order By: Relevance
“…The concept of pre-test counselling being provided by non-geneticists in order to streamline the process so that the genetics team are able to focus on mutation carriers rather than a cohort of patients, many of whom will not carry a mutation, is gathering general acceptance, with other studies demonstrating high levels of patient satisfaction. 31 Previous studies have identified higher mutation rates in patients with ovarian cancer than were identified in the east of Scotland, 19,26,32 but broadly similar to those in the west of Scotland. Many of these previous studies recruited patients retrospectively, however, and were based in tertiary referral centres that were not the sole providers of ovarian cancer care in their geographical location.…”
Section: Discussionmentioning
confidence: 90%
“…The concept of pre-test counselling being provided by non-geneticists in order to streamline the process so that the genetics team are able to focus on mutation carriers rather than a cohort of patients, many of whom will not carry a mutation, is gathering general acceptance, with other studies demonstrating high levels of patient satisfaction. 31 Previous studies have identified higher mutation rates in patients with ovarian cancer than were identified in the east of Scotland, 19,26,32 but broadly similar to those in the west of Scotland. Many of these previous studies recruited patients retrospectively, however, and were based in tertiary referral centres that were not the sole providers of ovarian cancer care in their geographical location.…”
Section: Discussionmentioning
confidence: 90%
“…For example, genetic testing may be ordered directly by oncologists and the oncology team, with support from clinical genetics. This model, often referred to as ‘mainstreaming’, was popularised by the Mainstreaming Cancer Genetics Programme in the UK 38. In the UK, implementation of the mainstreaming model resulted in a 100% genetic testing rate for women with non-mucinous ovarian cancer, with high patient and clinician satisfaction and reduced patient wait-times 38.…”
Section: National Priorities To Improve Assessment and Testing For Almentioning
confidence: 99%
“…However, the Mainstreaming Cancer Genetics programme has operated successfully including only one post-test counselling session for index individuals found to have a pathogenic BRCA mutation, one pretest counselling session for relatives and one post-test counselling session for relatives with the mutation. 190,191 Such a regime would reduce costs further, as generally half or fewer of those tested for LS mutations are found to have a pathogenic MMR mutation.…”
Section: Areas Of Uncertaintymentioning
confidence: 99%